Analisis Risiko Persepsian, Manfaat Persepsian, dan Kemudahan Penggunaan Persepsian Terhadap Penggunaan Paylater Pada E- commerce di Indonesia - Negoro, Aulia Rahmadiani; Achjari, Didi (Universitas Negeri Padang, 2024)
Purpose – This study examines the influence of perceived risk, perceived benefits, and perceived ease of use by customers that affect the use of paylater in e-commerce applications in IndonesiaDesign/methodology/approach – The data collection method used is an online survey method with a snowball sampling technique which is included in non-probability sampling by distributing questionnaires to 100 paylater user respondents who have used paylater at least once. The adopted model uses the Technology Acceptance Model (TAM) with a multivariate analysis method using Structural Equation Modeling Partial Least Square (SEM-PLS) with modifications to add perceived risk to it.Findings – This study found that perceived usefulness and perceived ease of use positively affect paylater usage; perceived ease of use has a positive effect on perceived usefulness; perceived risk negatively affects perceived usefulness; and perceived risk has a negative effect on paylater usage. The results of this study concluded that all hypotheses were supported.Originality/value – This research contributes, namely additional information to companies developing electronic payments (paylater) in considering user views of the paylater payment method in e-commerce applications in making future improvements.Research limitations/implications – This research has limitations, namely that it does not take into account the value or size of transactions and the socio-economic status of users in the research model. It is possible that these factors influenced or changed the results of this study. The greater transaction value can encourage users to use paylater. In addition, paylater is likely to attract more interest from users from lower socio-economic backgrounds. Future research is expected to examine aspects of transaction value and user socio-economic status when using paylater.